Changing bureaucracies : adapting to uncertainty, and how evaluation can help - Perrin, Burt; Tyrrell, Tony (New York, NY : Routledge, 2021)
"In Changing Bureaucracies, international experts provide an unparalleled look at how public sector bureaucracies can better adapt to the reality of unprecedented levels of uncertainty and complexity, and how they can better respond to the emerging needs and demands of citizens and beneficiaries. In particular, they discuss in detail how evaluation can play an important role in aiding bureaucracies in adapting, while noting that the value of evaluation is not at all automatic. Written in a clear and accessible prose, the contributors identify stability as a strength of bureaucratic structures, although adaptability is required in order to remain relevant. They also emphasize the need for bureaucratic rules and practices to be open to examination, such as through evaluation, noting that these rules may take on a life of their own, increasing distrust and conflicting with a meaningful focus on how outcomes and impacts benefit citizens. The book concludes with guidance for both evaluators and for public sector leaders about steps that they can take to improve the responsiveness and relevance of public sector organisations. Pioneering the provision of reflections on how evaluation can play an important role in aiding bureaucracies in adapting, Changing Bureaucracies is an important acquisition for public sector leaders, evaluators, evaluation managers and commissioners and academics alike"--
OCLC-licensed vendor bibliographic record.
Keywords: Public administration -- Evaluation; Bureaucracy -- Evaluation; Organizational change; POLITICAL SCIENCE / Public Policy / General; POLITICAL SCIENCE / Reference